2008
DOI: 10.1080/13625180802255701
|View full text |Cite
|
Sign up to set email alerts
|

Emergency contraception in South Africa: A literature review

Abstract: The existing literature suggests that the greater availability of EC is not sufficient to increase uptake and that interventions are needed to ensure that women become aware of this option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…8 In the present study, concerning dosage regimen of emergency contraception pills, it was identified that around half (48.6%) of the respondents knew the recommended time for emergency contraception pills to be within 72 hours, and 51.8% of them knew the dose and frequency of administration to be one tablet two times 12 hours apart. This finding slightly resembles the result from the study conducted in South Africa, 42% of the respondents know the correct time of taking emergency contraceptives after unprotected sexual intercourse 12 and a little bit higher than the study done among Swe-dish women where only less than 38% of the participants knew the recommended time frames for use. 13 The discrepancy between the result of current study and that of Swedish might be the difference between the educational backgrounds of the study participants where the present study was done on female college students and the study conducted in Swedish includes all type of females.…”
Section: Discussionsupporting
confidence: 79%
“…8 In the present study, concerning dosage regimen of emergency contraception pills, it was identified that around half (48.6%) of the respondents knew the recommended time for emergency contraception pills to be within 72 hours, and 51.8% of them knew the dose and frequency of administration to be one tablet two times 12 hours apart. This finding slightly resembles the result from the study conducted in South Africa, 42% of the respondents know the correct time of taking emergency contraceptives after unprotected sexual intercourse 12 and a little bit higher than the study done among Swe-dish women where only less than 38% of the participants knew the recommended time frames for use. 13 The discrepancy between the result of current study and that of Swedish might be the difference between the educational backgrounds of the study participants where the present study was done on female college students and the study conducted in Swedish includes all type of females.…”
Section: Discussionsupporting
confidence: 79%
“…Young, single women may face many barriers to accessing contraception including, for example, poor attitudes of nurses at clinics -some of whom believe that EC encourages promiscuity and that EC works as an abortifacient. 21 A study in Kenya found nurses' level of knowledge and attitudes to EC to be poor, which negatively influenced their decision to provide EC. 22 The lack of knowledge of healthcare professionals as well as their poor attitudes towards EC, which limit their willingness to prescribe EC, have been highlighted in a number of local and international studies, 4,20,23 and more information and training of healthcare professionals on EC has been recommended.…”
Section: Self-reported Knowledge Of Emergency Contraceptionmentioning
confidence: 99%
“…Yet, in many cases, inclusion in public sector guidelines is not enough to increase use. In South Africa, as documented by Maharaj (2008), EC is "available but not accessible (or promoted) to women who rely on public sector for health services." Additional efforts are necessary for improving availability and decreasing barriers to access.…”
Section: Inclusion In National Family Planning Programsmentioning
confidence: 99%